Tooth loss in adults: factors associated with the position and number of lost teeth - Valmir Vanderlei Gomes Filho; Brunna Verna Castro Gondinho; Manoelito Ferreira Silva-Junior; Denise de Fátima Barros Cavalcante; Jaqueline Vilela Bulgareli; Maria da Luz Rosario de Sousa; Antonio Carlos Frias; Marília Jesus Batista; Antonio Carlos Pereira (Universidade de São Paulo, 2019)
ABSTRACT OBJECTIVE To evaluate the factors associated with tooth loss in adults from the position and number of teeth lost in the dental arches. METHODS This is a cross-sectional, population-based study with adults participating in the epidemiological survey of oral health of São Paulo in 2015. The outcome of the study was tooth loss, assessed by the proposed classification, namely: I) lost up to 12 back teeth; II) lost up to 12 teeth (including front teeth); and III) lost more than 12 teeth. A four-block analysis was conducted, supported by a conceptual theoretical model adapted for tooth loss. For the multinomial logistic regression, "individuals who did not lose teeth due to caries or periodontal disease" was used as reference (p < 0.05). RESULTS Of 6,051 adults evaluated, 25.3% (n = 1,530) were classified in category I, 32.7% (n = 1,977) in II, 9.4% (n = 568) in III, and 1.9% (n = 117) were edentulous. Lower income and schooling, the perception of need for treatment and the last appointment motivated by routine, pain or extraction were associated with tooth loss, regardless of the classification. The negative evaluation of the dental service was associated with individuals who lost up to 12 teeth, both front and back. The presence of women and periodontal pocket were associated with tooth loss of up to 12 teeth, including front, and more than 12 teeth. Caries were associated with adults who lost up to 12 teeth, including front teeth. CONCLUSION The proposed classification allowed the identification of differences between the associated factors. Thus, the need to consider such classification in future studies is evident.